Sisterhood and Solidarity Workers' Education for Women, 1914-1984 - Frederickson, Mary; Kornbluh, Joyce L. (Temple University Press, 2018)
Sisterhood and Solidarity was one of the first volumes, and remains one of the few, to call attention to the importance of workers' education for women. The ten original essays, written by some of the best known labor and working-class history scholars of the time, analyze an educational experiment in which industrial, clerical, and service workers participated with educators, feminists, and social workers. This reissue appears at a time when a new generation of educators, activists, and researchers is revaluing workers' education, driven in part by the global rise of feminism and of female-led and female-majority worker movements. There's a new appreciation of the need for spaces where workers can recognize their own wisdoms; learn from the considered insights of others, past and present; and together rethink how to change society for the better. The essays in Sisterhood and Solidarity show that the value of workers' education for women was and continues to be key to ongoing progress. Rich in documentary materials from program archives, the chapter authors record how these nontraditional programs encouraged women workers to use their experiences with rural life, factory routine, and strikes to learn union skills and an understanding of the American economic system. Overcoming barriers of race, class, and region, these educational experiments are most notable as a widespread and sustained effort to empower women workers.